2011
DOI: 10.5194/acp-11-8363-2011
|View full text |Cite
|
Sign up to set email alerts
|

The variability of tropical ice cloud properties as a function of the large-scale context from ground-based radar-lidar observations over Darwin, Australia

Abstract: Abstract. The high complexity of cloud parameterizations now held in models puts more pressure on observational studies to provide useful means to evaluate them. One approach to the problem put forth in the modelling community is to evaluate under what atmospheric conditions the parameterizations fail to simulate the cloud properties and under what conditions they do a good job. It is the ambition of this paper to characterize the variability of the statistical properties of tropical ice clouds in different tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…The largest values of r ei are found for light easterly winds around 5-10 m s −1 for opaque, consistent with convectively active regimes generating larger r ei (e.g. Protat et al, 2011). Smaller values of a few µm are associated with westerly winds during suppressed convection.…”
Section: Dependence Of R Ei On Near Surface Wind Speedmentioning
confidence: 56%
See 2 more Smart Citations
“…The largest values of r ei are found for light easterly winds around 5-10 m s −1 for opaque, consistent with convectively active regimes generating larger r ei (e.g. Protat et al, 2011). Smaller values of a few µm are associated with westerly winds during suppressed convection.…”
Section: Dependence Of R Ei On Near Surface Wind Speedmentioning
confidence: 56%
“…Using ground-based retrievals at Darwin, Protat et al (2011) found that r ei is ∼ 1-3 µm larger during active deep convection compared to suppressed conditions. Using a simultaneous retrieval of ice cloud properties from the MODIS and POLDER instruments, van Diedenhoven et al (2014) found that r ei is larger in stronger convective events com- (2015) show similar results with DARDAR data for the thickest convective clouds above 10 km.…”
Section: Insight Into Convective Processes With Amsrmentioning
confidence: 99%
See 1 more Smart Citation
“…The AMSR low frequency (LF) wind is 25 used to quantify the response of r ei to variability in near surface wind speeds in the presence of convection. regimes generating larger r ei (e.g., Protat et al, 2011). Smaller values of r ei are associated with westerly winds during suppressed convection.…”
Section: Dependence Of R Ei On Near Surface Wind Speedmentioning
confidence: 99%
“…Using ground-based retrievals at Darwin, Protat et al (2011) found that r ei is ~1-3 µm larger during active deep convection compared to suppressed conditions. Using a simultaneous retrieval of ice cloud properties from the MODIS and POLDER 20 instruments, van Diedenhoven et al (2014) found that r ei is larger in stronger convective events compared to others at a given cloud top pressure.…”
Section: Insight Into Convective Processes With Amsrmentioning
confidence: 99%